Effects of light on the growth and production of edible shoots of rattan - C. Renuka (2016)
Studies on three species of edible rattan occurring in the Western Ghats, Calamus thwaitesii, C. hookerianus and C. metzianus, under different light conditions showed that light intensity had effects on survival percentage, growth and number of shoots produced. In C. hookerianus, maximum survival was obtained under 75% light while in C. thwaitesii and C. metzianus, under 50%. The number of shoots produced was greater under 50% light in all the species. Light and period greatly affected the percentage survival of C. hookerianus. The effects of light intensities on height growth and number of shoots produced in C. hookerianus and C. thwaitesii were considerable, while those in C. metzianus, negligible. In an agroforestry system of the three species studied, C. metzianus is best suited for shoot production since it performs well under 100, 75 and 50% light.